Acute effect of different elasticity resistance bands with plyometric exercise on power performance among UiTM Seremban 3 volleyball player - Abdul Taufeq, Muhammad Afham Wajdi; Mohd Nasir, Muhammad Zulqarnain (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study examines how combining plyometric exercises with different resistance band intensities (lightweight vs. medium-weight) affects the power performance of 20 male amateur volleyball players at UiTM Seremban 3. Utilizing a randomized crossover design with a one-week washout period, the research addresses a gap in literature often focused on elite athletes by measuring vertical and broad jump improvements in a non-elite population. Results, captured via Vertec and standing broad jump tests, aim to identify the most effective resistance-plyometric combination for enhancing explosive strength.